ASHRAE handbook. Heating, ventilating, and air-conditioning systems and applications. - American Society of Heating, Refrigerating and Air-Conditioning Engineers (Atlanta, Ga. American Society of Heating, Refrigerating and Air Conditioning Engineers, 1987)
Quadrennial.
Continues in part (formed from revised and combined chapters of): ASHRAE handbook. Applications; and: ASHRAE handbook. Systems.
Split into: ASHRAE handbook. Heating, ventilating, and air-conditioning applications (Inch-pound ed.); ASHRAE handbook. Heating, ventilating, and air-conditioning applications (SI ed.); and: ASHRAE handbook. Heating, ventilating, and air-conditioning systems and equipment (Inch-pound ed.); and: ASHRAE handbook. Heating, ventilating, and air-conditioning systems and equipment (SI ed.)
Keywords: Heating -- Handbooks, manuals, etc; Air conditioning -- Handbooks, manuals, etc; Ventilation -- Handbooks, manuals, etc